Associations between repetitive head impact exposure and midlife mental health wellbeing in former amateur athletes - Buddenbaum, Claire V.; Recht, Grace O.; Rodriguez, Adriana K.; Newman, Sharlene D.; Kawata, Keisuke (Frontiers in Psychiatry, 2024)
Repetitive head impacts (RHI) have been suggested to increase the risk of developing a neurodegenerative disease, and many of these individuals develop a preceding mental health diagnosis. Given the lack of studies among amateur athletes, this study aimed to examine mental health outcomes in middle-aged amateur athletes who have been exposed to RHI through contact sport participation. Methods: This is a single site, cohort study involving former amateur athletes aged between 30 and 60 with at least 10 years of organized contact or non-contact sport participation. All participants completed demographic and mental health questionnaires. Mental health outcomes included symptoms related to depression, anxiety, post-traumatic stress disorder (PTSD), attention deficit hyperactive disorder (ADHD), and aggression. Self-reported data on mental health diagnoses and associated prescription were elicited and used to estimate odds ratios (OR). Results: Data from 39 contact athletes and 21 age/sex-matched non-contact athletes were available for analysis. The contact group exhibited a 2.25-fold higher likelihood of being diagnosed with mental health disorders and 1.29-fold higher likelihood of using associated medications compared to the non-contact group. The contact group reported significantly higher PTSD-related symptoms [4.61 (0.03,9.2), p=0.05] compared to the non-contact control group. While not statistically significant, the contact group showed increased depressive [2.37 (0.05, 4.79), p=0.07] and ADHD symptoms [4.53 (0.51, 9.57), p=0.08] compared to controls. In a secondary analysis, a distinct trend emerged within the contact group, revealing pronounced elevations in mental health symptoms among individuals with lower socioeconomic status (<50,000/year) compared to higher income subgroups, and these symptoms decreased as income levels rose [depression: -3.08 p<0.001; p=0.002; p=0.004; p=0.003; p=0.01]. This trend was absent in the non-contact control group. Discussion: Our data suggest that even individuals at the amateur level of contact sports have an increased likelihood of being diagnosed with mental health disorders or experiencing mental health symptoms compared to non-contact athletes. Our findings indicate that socioeconomic status may have an interactive effect on individuals' mental health, particularly among those with a long history of RHI exposure.